Integrating Passenger and Modulo as Learning Tools for Collaborative Engineering Education - Ramli, Kalamullah; Schwarz, Frank; Werner, Stefan; Shamsuddin, A Halim; Hunger, Axel (UI Scholars Hub, 2002)
The University of Indonesia (UI), Gerhard Mercator University (GMU), the Universiti Kebangsaan Malaysia (UKM) have agreed to cooperate as partners to develop a joint bachelor (3+1) and masters (1+1) degree, and collaborate in the research fi elds of multimedia- and internet-based learning and application level active networks. This paper describes the introduction of the Offshore Project and the extending of information technology applications to the partner institutions in this international cooperation which would very much enhance the operations of the new initiative in engineering education, which could provide students in far distance with more fl exible learning environment.